2023
DOI: 10.5194/egusphere-2023-311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Iodine oxoacids and their roles in sub-3 nanometer particle growth in polluted urban environments

Abstract: Abstract. New particle formation processes contribute significantly to the number concentration of ultrafine particles (UFP), and have great impacts on human health and global climate. Iodine oxoacids (HIOx, including iodic acid, HIO3 and iodous acid, HIO2) have been observed in pristine regions and proved to dominate NPF events at some sites. However, the knowledge of HIOx in polluted urban areas is rather limited. Here, we conducted a long-term comprehensive observation of gaseous iodine oxoacids and sulfuri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…For instance, a potentially influential process is coagulation, wherein large particles can grow by scavenging small particles . Meanwhile, other inorganic vapors including iodine oxoacid (HIO 3 ), nitric acid (HNO 3 ), and ammonia (NH 3 ) may also promote nanoparticle growth under specific environments, but their influence on the growth of 4–40 nm particles is limited in most cases. , Besides, heterogeneous reactions may also slightly impact nanoparticle growth by either increasing or decreasing the particle-phase species . Observed GRs may also have some uncertainty due to instrument, sampling, or computational errors, affecting the validation of simulation GRs. However, our purpose here is not to comprehensively describe all the detailed mechanisms relevant to nanoparticle growth but rather to find out the main species and processes that contribute to nanoparticle growth and establish a prediction method for GRs.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a potentially influential process is coagulation, wherein large particles can grow by scavenging small particles . Meanwhile, other inorganic vapors including iodine oxoacid (HIO 3 ), nitric acid (HNO 3 ), and ammonia (NH 3 ) may also promote nanoparticle growth under specific environments, but their influence on the growth of 4–40 nm particles is limited in most cases. , Besides, heterogeneous reactions may also slightly impact nanoparticle growth by either increasing or decreasing the particle-phase species . Observed GRs may also have some uncertainty due to instrument, sampling, or computational errors, affecting the validation of simulation GRs. However, our purpose here is not to comprehensively describe all the detailed mechanisms relevant to nanoparticle growth but rather to find out the main species and processes that contribute to nanoparticle growth and establish a prediction method for GRs.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study based on long-term observations found that [IA] can reach about 2.8 × 10 6 cm −3 in the polluted urban atmosphere in Beijing and Nanjing. 23 As shown in Figure 6B, DEA with a ppt level can lead to notable J values (>10 cm −3 s −1 ) when [IA] is about 10 6 cm −3 . In fact, DEA at ppt levels has been detected in polluted urban atmospheres, including Beijing.…”
Section: ■ Introductionmentioning
confidence: 89%
“…18 However, the current knowledge may not well predict IA-induced nucleation under all circumstances, especially in chemically complex polluted and semi-polluted environments. As the presence of iodine species in polluted environments has been unambiguously revealed, 14,23 it is necessary to investigate the enhancing potential of other compounds on IA-induced nucleation, with special attention to compounds with stronger enhancing potential compared to HIO 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 This simple and efficient production pathway of HIO 3 may help explain the ubiquitous presence of HIO 3 globally, 16 even including inland polluted cities such as Beijing and Nanjing. 33 The CLOUD experiment has also revealed that HIO 3 alone is not able to explain iodine particle formation and HIO 2 is needed to form the initial clusters together with HIO 3 (termed the iodine oxoacid nucleation mechanism). 16 Recent theoretical work utilising quantum chemical calculations and kinetic simulations further uncovered the critical role of HIO 2 in stabilising HIO 3 clusters because HIO 2 exhibits strong alkalinelike behaviour.…”
Section: Introductionmentioning
confidence: 99%